Knowledge on Blood Donation among Nursing Students - Priyadharshini, R. (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2023)
Background: Blood donation has the potential to save a dying life. India, being the second most populated country with ample number of youth’ voluntary non-remunerated blood donations should be increased. The nursing students being an important member of the frontline health worker need to be aware of the blood donation. The nurses being the heart of the health care team need to donate blood and at the same time, they need to create awareness among the public. Methodology: A pre-experimental one-group pre-test post-test research design was adopted for this study with a total of 30 nursing students selected through non-probability purposive sampling technique from the College of Nursing: East Coast Institute of Medical Sciences at Puducherry. Data was collected using a Structured Knowledge questionnaire which comprised of Socio-demographic profile and a Questionnaire on Blood Donation. Result: The study findings revealed that the pretest mean score of knowledge was 6.03 with a standard deviation of 2.32 and the post-test mean score of knowledge was 16.82 with a standard deviation of 2.91. The calculated paired t-test value of t = 21.601 was found to be statistically highly significant at p<0.001 level. This infers that there was significant improvement observed in the post-test level of knowledge among B.Sc. Nursing students. Conclusion: The findings showed that the Structured Teaching Programme on knowledge regarding Blood donation was found to be effective in improving the level of knowledge in the post-test.